Jump in the fire — heat shock proteins and their impact on ovarian cancer therapy. (January 2016) - Stope, M.B.; Koensgen, D.; Burchardt, M.; Concin, N.; Zygmunt, M.; Mustea, A.
Abstract: Ovarian cancer (OC) is a major problem in gynecological oncology. Options for diagnosis and treatment of advanced stages and thus for patient prognosis have not been improved substantially over the past decades. Heat shock proteins (HSP) are characterized as stress-induced molecular chaperones performing cell survival factor functions. In cancer cells, various crucial and clinically important cell responses are vitally influenced and modulated by HSPs, e.g., cell growth and treatment resistance. Despite the limited knowledge on HSPs in OC progression, their roles as biomarkers, prognostic factors and their drug target properties appears promising for future clinical applications and therapeutic approaches.